Evolutionary Developmental Biology (Evo‐Devo) Research in Latin America. Issue 1 (5th August 2016) - Marcellini, Sylvain; González, Favio; Sarrazin, Andres F.; Pabón‐Mora, Natalia; Benítez, Mariana; Piñeyro‐Nelson, Alma; Rezende, Gustavo L.; Maldonado, Ernesto; Schneider, Patricia Neiva; Grizante, Mariana B.; Da Fonseca, Rodrigo Nunes; Vergara‐Silva, Francisco; et al.
ABSTRACT: Famous for its blind cavefish and Darwin's finches, Latin America is home to some of the richest biodiversity hotspots of our planet. The Latin American fauna and flora inspired and captivated naturalists from the nineteenth and twentieth centuries, including such notable pioneers such as Fritz Müller, Florentino Ameghino, and Léon Croizat who made a significant contribution to the study of embryology and evolutionary thinking. But, what are the historical and present contributions of the Latin American scientific community to Evo‐Devo? Here, we provide the first comprehensive overview of the Evo‐Devo laboratories based in Latin America and describe current lines of research based on endemic species, focusing on body plans and patterning, systematics, physiology, computational modeling approaches, ecology, and domestication. Literature searches reveal that Evo‐Devo in Latin America is still in its early days; while showing encouraging indicators of productivity, it has not stabilized yet, because it relies on few and sparsely distributed laboratories. Coping with the rapid changes in national scientific policies and contributing to solve social and health issues specific to each region are among the main challenges faced by Latin American researchers. The 2015 inaugural meeting of the Pan‐American Society for Evolutionary Developmental Biology played a pivotal role in bringing together Latin American researchers eager to initiate and consolidate regional and worldwide collaborative networks. Such networks will undoubtedly advance research on the extremely high genetic and phenotypic biodiversity of Latin America, bound to be an almost infinite source of amazement and fascinating findings for the Evo‐Devo community.